Children's perspectives of primary school environments - Woods, Lois (2018)
It has been recognised for many years that children learn from direct experiences with their surrounding environments (Weinstein and David, 1987). Considering children spend the majority of their early lives occupying school buildings, the quality of this built environment is important as it is thought to have an impact on their learning, social development and well-being. The architectural design of school environments, procured over the past 15 years has been constantly evolving with the need for new and improved school buildings coupled with significant changes in education over the past few decades.